Stability in the production and transport of 177Lu labelled PSMA (Brazilian Journal of Radiation Sciences, 2021)
The prostate cancer is the second most prevalent disease among men in Brazil, moreover PSMA therapy could change this scenario and its perspectives. IPEN-CNEN is the Brazilian industrial radiopharmacy center that produces radiopharmaceuticals for therapy. The production of 177Lu-PSMA-617 was evaluated in batches until 37 GBq and showed that the combination of ascorbate buffer, adequate radioactive concentration and freezing promoted the stability of the radiopharmaceutical for 48 hours, enabling transport of 177Lu-PSMA-617 to distant regions of the country.